2004
DOI: 10.1038/sj.jhh.1001684
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and baroreflex sensitivity in healthy subjects and patients with mild-to-moderate hypertension

Abstract: Decreased baroreflex sensitivity (BRS) is a prognostic marker in essential hypertension. Animal experiments suggest that decreased BRS is related to increased oxidative stress. Our study was aimed at testing whether oxidative stress, estimated by isoprostane 15-F 2t -IsoP urinary levels, is correlated to BRS variation in healthy subjects as well as in patients suffering from essential hypertension. Urinary 15-F 2t -IsoP levels and BRS were evaluated in two groups of subjects: healthy volunteers (n ¼ 64) and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…These correlations indicate that the effect of exercise training on oxidative stress plays an important role in the improvement of BRS. These results agree with other studies, which have also evidenced a relationship between oxidative stress and BRS in healthy individuals and patients with mild to moderate hypertension [36], human chronic heart failure [37], experimental adryamicin-induced heart failure [16], and in ovariectomized rats [14]. However, few studies have shown the influence of different antioxidant interventions such as vitamin C [15,37], vitamin E [38], N-acetylcysteine and melatonin [39] in the association of oxidative stress and BRS.…”
Section: Discussionsupporting
confidence: 92%
“…These correlations indicate that the effect of exercise training on oxidative stress plays an important role in the improvement of BRS. These results agree with other studies, which have also evidenced a relationship between oxidative stress and BRS in healthy individuals and patients with mild to moderate hypertension [36], human chronic heart failure [37], experimental adryamicin-induced heart failure [16], and in ovariectomized rats [14]. However, few studies have shown the influence of different antioxidant interventions such as vitamin C [15,37], vitamin E [38], N-acetylcysteine and melatonin [39] in the association of oxidative stress and BRS.…”
Section: Discussionsupporting
confidence: 92%
“…The "weak" version of the oxidative stress theory postulates that oxidative damage is causative of or associated with age-related diseases. Indeed, there are numerous diseases/conditions that develop in aged individuals that have, at least as part of their basis, free radical damage [5][6][7][8]. These conditions eventually compromise the health of an organism and, ultimately, death follows.…”
Section: Introductionmentioning
confidence: 99%